Goin' International Raton's Fireballs hit foreign CD market - Mullings, David (Raton, NM Raton Range, 1992)
This article is about the Fireballs' music selling overseas bringing new life to their music.
Newspaper article + Photograph of George Tomsco and Chuck Tharp
Mater List Item # 29
File location is in the Raton File Cabinet
Keywords: Tomsco, George; Tharp, Chuck; Williston, Clyde; Fireballs; Williston Studios; Musical Groups; Music Sales; Music CDs; Local Bands; Raton, New Mexico